Novel non-noble metal catalyst with high efficiency and synergetic photocatalytic hydrolysis of ammonia borane and mechanism investigation. (1st April 2022) - Fang, Ruiming; Yang, Zhongqing; Wang, Ziqi; Ran, Jingyu; Yan, Yunfei; Zhang, Li
Abstract: Herein, we successfully prepared a highly active non-noble metal CuNi/CNS, as a highly efficient synergistic catalyst for the hydrolysis of ammonia borane to hydrogen. 9.36% CuNi alloy nanoparticles loaded on the surface of g-C3 N4 nanosheets at the molar ratio of 1:1 showed excellent photocatalytic activity for the hydrolysis of AB, and their TOF values under dark/visible light excitation were 12.6 and 26.6, respectively. Furthermore, after five cycles, the hydrogen production of Cu0.5 Ni0.5 /CNS in 10 min is only 5% lower than that of the fresh catalyst, fully demonstrating that the catalyst has excellent reusability. Photoelectrochemical characterizations and theoretical results indicate that the transition metal nanoparticles deposited on the g-C3 N4 nanosheets modified the band structure, the bandgap value of 2.77 eV (CNS) reduce to 2.58 eV (Cu/CNS), 2.55 eV (Ni/CNS) and 2.52 eV (Cu0.5 Ni0.5 /CNS). The 3 d orbits of Cu and Ni are mainly involved in the valence band composition of the catalyst system, which not only greatly changes the original orbital structure, reduces the bandgap, but also enhances the transmission of photoelectron and hole pair between the triazine rings. In addition, the synergistic effect of alloy effect, Mott-Schottky junction and the LSPR effect improve the photocatalytic activity of the CuNi/CNS catalyst. Highlights: Cu0.5 Ni0.5 /CNS can achieve noble metal-like catalytic activity. The 3 d orbits of alloy phase are mainly involved in the valence band composition. CuNi alloy enhances the transmission of photocarriers between the triazine rings. Schottky junction, LSPR and alloy effect jointly promote the catalytic activity.